Diagnosis and treatment planning using the 2017 classification of periodontal diseases among three dental schools. Issue 11 (29th May 2022) - Gandhi, Kaveri K.; Katwal, Diksha; Chang, Jennifer; Blanchard, Steven; Shin, Daniel; Maupome, Gerardo; Eckert, George J.; John, Vanchit
Abstract: Objectives: The American Academy of Periodontology and the European Federation of Periodontology developed a new classification system for periodontal diseases in 2017. The next step in its widespread implementation involves training dental students to improve consistency in clinical decisions. This study conducted in 2020–2021 aimed to evaluate knowledge in periodontal diagnosis and treatment planning using the new classification, among first, second, third‐ and fourth‐year dental students at Indiana University School of Dentistry (IUSD), University of Texas School of Dentistry at Houston (UTSD), and University of Louisville School of Dentistry (ULSD). Methods: A minimum of 20 dental students per class year from each of the three schools participated. Ten HIPPA de‐identified case records and a questionnaire with a fixed list of answer options, comprising two demographic questions and two questions on diagnosis and treatment planning of each case, were presented to the participants. A group of three board‐certified periodontists established the answers for all cases which were used to score the appropriateness of diagnosis and treatment planning among the participants. Results: A total of 263 students participated. Overall, 22.6% of IUSD responses, 25.2% of UTSD, and 27.6% of ULSD responses were correct for diagnosis (no statistically significant differences). For the treatment plan, 64.9% of IUSD responses, 66.2% of UTSD, and 68.9% of ULSD responses were correct (no statistically significant differences). Conclusion: Based on the findings from our study, we suggest that additional training be considered to improve the understanding of the 2017 classification of periodontal and peri‐implant diseases among dental students.